R-spondins function as ligands of the orphan receptors LGR4 and LGR5 to regulate Wnt/β-catenin signaling - Carmon, Kendra S. (National Academy of Sciences, 2011)
The Wnt/β-catenin signaling system plays essential roles in embryonic development and in the self-renewal and maintenance of adult stem cells. R-spondins (RSPOs) are a group of secreted proteins that enhance Wnt/β-catenin signaling and have pleiotropic functions in development and stem cell growth. LGR5, an orphan receptor of the G protein-coupled receptor (GPCR) superfamily, is specifically expressed in stem cells of the intestinal crypt and hair follicle. Knockout of LGR5 in the mouse results in neonatal lethality. LGR4, a receptor closely related to LGR5, also has essential roles in development, as its knockout leads to reduced viability and retarded growth. Overexpression of both receptors has been reported in several types of cancer. Here we demonstrate that LGR4 and LGR5 bind the R-spondins with high affinity and mediate the potentiation of Wnt/β-catenin signaling by enhancing Wnt-induced LRP6 phosphorylation. Interestingly, neither receptor is coupled to heterotrimeric G proteins or to β-arrestin when stimulated by the R-spondins, indicating a unique mechanism of action. The findings provide a basis for stem cell-specific effects of Wnt/β-catenin signaling and for the broad range of functions LGR4, LGR5, and the R-spondins have in normal and malignant growth.